Response of high-strength concrete beams with corrugated discrete steel fibers to small shear span-depth ratios - Alzara, Majed; Yosri, Ahmed M.; Yousef, Saif Eldeen A. S.; Deifalla, Ahmed Farouk (Frontiers in Built Environment, 2023)
The behavior of high-strength, fiber-reinforced concrete (HSFRC) beams under concentrated loads was affected by many different aspects, such as the type of fibers used and the volume percent of the fibers; nevertheless, the behavior was primarily affected by modifying the shear span-to-depth ratio (a/d). In this experimental investigation, the influence of a/d ratios (ranging from 1.5 to 2.2) is investigated on the response of twelve high-strength fiber-reinforced concrete (HSFRC) beams containing varying amounts of discontinuous steel fiber (VF) in the concrete mixture. The purpose of this study was to analyze the manner of failures of the tested beams and to identify a limiting a/d for effective beam depth. Shear failure was observed in high-strength concrete (HSRC) beams with a vf of 0% at a/d ratios as high as 2.2, according to the study's findings of the study. Altering either the a/d ratios or the vf had an effect on the way in which the HSFRC beams responded to the stimulus. Some of the HSFRC beams that were put through the shear–flexure test failed. In addition, the findings demonstrated that, as the a/d ratio increased up to 2.2, the beams with a vf of 0.5% and 0.75% broke in pure flexure with multi-cracking. This indicates that the a/d ratio has a substantial impact on the various failure behaviors of HSFRC beams.T